Carbon nanotube enhanced printed Li-ion cathodes - Lee, Ying Wei. (2010)
Energy storage is unable to keep up with the shrinking size of consumer electronic. A simple method is used to create a thin film battery. The electrodes materials comprises of active material,75wt% (lithium cobalt oxide (LiCoO2) and lithium iron phosphate (LiFePO4) for cathode; graphite for anode) polyvinylidene fluoride (PVDF),15wt% and carbon black (CB),10wt% were prepared into a paste and printed with a doctor blade. The coating was then dried, cut into 16mm round electrodes and assembled into coin cells for testing. The capacity achieved by the LiCoO2 and LiFePO4 cells was 106mAh/g and 66mAh/g respectively. LiFePO4 has a higher theoretical capacity but does not perform as expected due to the low intrinsic conductivity. In order to improve the conductivity of LiFePO4, additional conductive additive were added by decreasing the active material to improve the conductivity. With 5wt% carbon nanotube(CNT) added to the paste, the capacity increased to 103mAh/g. Addition amount of carbon black amounting to 20wt% was added to the paste, the capacity only increase to 74mAh/g. The difference in performance achieved by the CNT and CB cells is an indication in the improvement of the conductivity. A higher capacity related to a higher conductivity. The conductivity improvement achieved by CNT is much better than that of CB. In order to further confirm the improvement, a reduced carbon content composition was tested, 5wt% CB with 5wt%CNT. The achieved capacity was 96mAh/g. This further confirms that CB does not increase the conductivity as much as CNT. The results were then plotted into a ragone graph; LiFePO4 with CNT has the highest energy density while LiCoO2 has the highest power density.